A non-aqueous electrolyte and lithium ion battery

By using lithium oxalate salt and nitrile or unsaturated phosphate additives in non-aqueous electrolyte in lithium-ion batteries, an anti-corrosion film is formed, which solves the problem of corrosion of nickel-plated steel shells under high voltage and increases the high temperature of the battery Cycle stability and safety.

CN114597488BActive Publication Date: 2024-12-13SHENZHEN CAPCHEM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202011407729.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-04
Publication Date
2024-12-13
Estimated Expiration
2040-12-04

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, nickel-plated steel shells are prone to corrosion at high voltages, resulting in the risk of liquid leakage and lithium extraction, increasing safety risks, and the battery performance declines after high temperature circulation.

Method used

A non-aqueous electrolyte is adopted, which contains lithium salt, non-aqueous organic solvent, lithium oxalate-type additives and nitrile additives or phosphate esters containing unsaturated bonds. Through synergistic action, it forms an anti-corrosion film to inhibit nickel and iron. corrosion and improve the battery's high temperature cycle stability.

Benefits of technology

It significantly improves the corrosion resistance of nickel-plated steel shells, reduces the deposition of nickel and iron, reduces the risk of lithium excretion, extends the high-temperature cycle life of the battery, and maintains a low impedance growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002817704090000101
    Figure BDA0002817704090000101
  • Figure BDA0002817704090000111
    Figure BDA0002817704090000111
  • Figure BDA0002817704090000121
    Figure BDA0002817704090000121
Patent Text Reader

Abstract

The present application discloses a non-aqueous electrolyte and a lithium-ion battery. The non-aqueous electrolyte of the present application is used for nickel-plated steel shell lithium-ion batteries, which includes a lithium salt, a non-aqueous organic solvent and an additive accounting for 0.2%-20% of the mass of the non-aqueous electrolyte; the lithium salt includes lithium hexafluorophosphate; the additive includes a first additive and a second additive; the first additive is at least one of lithium difluorooxalate borate, lithium dioxalate borate and lithium difluorobisoxalate phosphate; the second additive is at least one of a nitrile additive and a phosphate containing an unsaturated bond. The non-aqueous electrolyte of the present application uses the first additive to inhibit HF generation and play an anti-corrosion role, and uses the second additive to form a film layer to enhance the anti-corrosion effect; and uses the electronegativity of the first additive to participate in and optimize the composition and structure of the film layer formed by the second additive, further enhancing the anti-corrosion effect, and improving the battery performance, especially improving the high-temperature cycle stability, and reducing the impedance growth after high-temperature cycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery electrolytes, and in particular to a non-aqueous electrolyte and a lithium-ion battery. Background Art

[0002] At present, common lithium-ion battery shell materials on the market include steel shells and aluminum shells. Although aluminum shells have the advantages of light weight and higher expansion coefficient, which reduces the risk of explosion when the battery is short-circuited, the physical stability and high strength characteristics of steel materials cannot be replaced. The advantages of steel shells are further amplified in cylindrical batteries, because the cylindrical sides can distribute the pressure, improving the safety performance of the battery when encountering strong squeezing. At the same time, the manufacturing process of steel shells in cylindrical batteries is more mature, further reducing production costs. Therefore, lithium-ion batteries with steel shells as the base have a wide range of applications. For example, Tesla has selected cylindrical lithium-ion batteries with steel shells as the base, giving full play to its mature technology, high degree of industrial automation, and good safety.

[0003] As the base material of lithium-ion batteries, steel shells need to be treated with nickel plating to improve the surface gloss and aesthetics, while also improving its wear resistance and corrosion resistance. If the nickel plating of the steel shell falls off, it will cause corrosion of the steel shell, posing a huge safety hazard to the battery. Currently, high-performance nickel-plated steel shell lithium-ion batteries all use an iron-nickel diffusion layer model, which effectively ensures the density, adhesion, and synchronous extensibility of the plating.

[0004] The main components of existing electrolytes include lithium hexafluorophosphate (LiPF6). LiPF6 will accelerate decomposition to generate byproducts under high voltage, increasing the corrosion of the nickel metal on the inner wall of the steel shell; once the nickel metal is corroded, the exposed iron element of the steel shell is more active and will be further corroded quickly, thereby increasing the risk of leakage of the steel shell. In addition, the nickel ions and iron ions formed after corrosion dissolve into the electrolyte and will be reduced and deposited at the negative electrode, blocking the conduction path of lithium ions, thereby increasing the risk of lithium precipitation and safety hazards.

[0005] Therefore, developing a lithium-ion battery electrolyte that prevents corrosion of nickel-plated steel shells remains an urgent problem to be solved in related research fields. Summary of the invention

[0006] The purpose of the present application is to provide an improved non-aqueous electrolyte and a lithium-ion battery using the non-aqueous electrolyte.

[0007] In order to achieve the above objectives, this application adopts the following technical solutions:

[0008] One aspect of the present application discloses a non-aqueous electrolyte, which is used for a lithium-ion battery whose shell is a nickel-plated steel shell. The non-aqueous electrolyte includes a lithium salt, a non-aqueous organic solvent, and an additive accounting for 0.2%-20% of the total mass of the non-aqueous electrolyte; wherein the lithium salt includes lithium hexafluorophosphate; the additive includes a first additive and a second additive; the first additive is at least one of lithium difluorooxalatoborate (LiODFB), lithium dioxalatoborate (LiBOB) and lithium difluorobisoxalatophosphate (LiDFOP); the second additive is at least one of a nitrile additive and a phosphate containing an unsaturated bond (hereinafter referred to as an unsaturated phosphate).

[0009] It should be noted that the key to the non-aqueous electrolyte of the present application is the use of the first additive and the second additive in combination. The first additive and the second additive themselves have certain anti-corrosion effects, especially the second additive can form an anti-corrosion film; however, the present application utilizes the synergistic effect of the first additive and the second additive to further enhance the anti-corrosion effect and improve battery performance. Specifically, the electronegativity of the first additive is utilized to participate in and optimize the anti-corrosion film formed by the second additive, thereby improving the anti-corrosion effect and improving battery performance. The detailed analysis is as follows:

[0010] The first additive of the present application is a specially selected oxalate inorganic lithium salt additive. The oxalic acid ligand of these three additives is a Lewis base as an electron-donating group, and phosphorus pentafluoride is a strong Lewis acid. When the electrolyte contains a lithium salt additive of oxalic acid ligand, the oxalic acid ligand reacts with phosphorus pentafluoride generated by hexafluorophosphate to generate LiPF4C2O4 and LiBF4, effectively preventing the generation of PF5, and then inhibiting the reaction with trace water in the electrolyte to generate trifluorophosphorus oxyfluoride POF3 and hydrogen fluoride HF, while preventing the electrolyte from oxidative decomposition, it also prevents hydrofluoric acid from corroding the steel shell. In the second additive, nitrile additives and phosphates containing unsaturated bonds can form a passivation film alone, which has an anti-corrosion effect. Specifically, nitrile additives have an electronegativity comparable to that of halogen chloride ions due to the presence of cyano groups, so they can form a strong bond with low-valent metal ions. When the electrolyte contains nitrile additives, the nickel ions formed by the corrosion of the steel shell surface by hydrofluoric acid HF interact with the cyanide of the nitrile additive to form a coordination polymer passivation film of Ni-X-PF6 attached to the surface of the steel shell, where X is the nitrile additive. This passivation film can effectively inhibit the dissolution of nickel and prevent further corrosion of the steel shell. Phosphates containing unsaturated bonds contain multiple acetylenes and alkenes, and the HOMO energy level of their compounds is higher than that of commonly used solvents in electrolytes, such as ethylene carbonate, dimethyl carbonate, diethyl carbonate, etc. When the electrolyte contains unsaturated phosphates, this type of additive is the first to undergo oxidation reaction during the battery cycle; its oxidation products polymerize on the surface of the steel shell to form a dense organic polymer film layer, which prevents substances such as hydrogen fluoride in the electrolyte from corroding the surface of the steel shell. The present application creatively combines the first additive and the second additive, and utilizes the electronegativity of the lithium salt additive of the oxalic acid ligand to combine with the nickel ions corroded by HF on the surface of the steel shell, and participates in and optimizes the composition and structure of the film layer formed by the second additive on the surface of the steel shell, thereby further enhancing the anti-corrosion effect and improving the performance of the battery, especially improving the high-temperature cycle stability of the battery and reducing the impedance growth after high-temperature cycling. In one implementation of the present application, after 800 cycles of high-temperature cycling at 45°C, the capacity retention rate can still reach 89.2%, and the impedance increase is only 13.7%.

[0011] It can be understood that the key to the present application lies in the combined use of the first additive and the second additive, and the non-aqueous organic solvent can refer to the prior art. However, in order to further improve and ensure the anti-corrosion effect, the non-aqueous organic solvent is limited in the preferred technical solution of the present application, as detailed in the following technical solution.

[0012] It should also be noted that, according to the above analysis, the non-aqueous electrolyte of the present application is particularly suitable for lithium-ion batteries using nickel-plated steel shells as outer shells; however, it can be understood that the non-aqueous electrolyte of the present application is not limited to lithium-ion batteries with nickel-plated steel shells as outer shells, and no specific limitation is made here.

[0013] In one implementation of the present application, the first additive accounts for 0.1%-10% of the total mass of the non-aqueous electrolyte, and the second additive accounts for 0.1%-10% of the total mass of the non-aqueous electrolyte.

[0014] Preferably, the second additive consists of a nitrile additive and a phosphoric acid ester containing an unsaturated bond.

[0015] More preferably, the first additive accounts for 0.2%-8% of the total mass of the non-aqueous electrolyte, the nitrile additive accounts for 0.05%-8% of the total mass of the non-aqueous electrolyte, and the phosphate containing unsaturated bonds accounts for 0.05%-8% of the total mass of the non-aqueous electrolyte.

[0016] More preferably, the first additive accounts for 0.2%-5% of the total mass of the non-aqueous electrolyte, the nitrile additive accounts for 0.1%-5% of the total mass of the non-aqueous electrolyte, and the phosphate containing unsaturated bonds accounts for 0.1%-5% of the total mass of the non-aqueous electrolyte.

[0017] It should be noted that in one implementation of the present application, an inorganic lithium salt-type oxalate additive, a nitrile additive and a phosphate containing an unsaturated bond are used in combination, and the comprehensive utilization of the nitrile additive and the phosphate containing an unsaturated bond can form the performance of the film layer; the synergistic effect of the three can form a film layer with better anti-corrosion effect, thereby further improving the anti-corrosion performance of the nickel-plated steel shell.

[0018] It can be understood that the key to this application lies in the combined use of the first additive and the second additive. In principle, as long as the non-aqueous electrolyte contains the first additive and the second additive, it can more or less play an anti-corrosion effect; however, the experiment found that the dosage of the inorganic lithium salt oxalate additive can be 0.1%-10%, preferably 0.2%-8%, and more preferably 0.2%-5%. Among them, when the dosage is 0.2%-5%, the capacity retention rate of 800 cycles at 45°C high temperature is high, and the impedance growth after high temperature cycling is small. Similarly, the dosage of nitrile additives can be 0.05%-8%, but when the dosage is 0.1%-5%, better high temperature cycle capacity retention rate and smaller impedance growth can be obtained; the dosage of unsaturated phosphate esters can be 0.05%-8%, but when the dosage is 0.1%-5%, better high temperature cycle capacity retention rate and smaller impedance growth can be obtained.

[0019] In one implementation of the present application, the phosphate containing an unsaturated bond is at least one of the compounds shown in Structural Formula 1;

[0020] Structural formula 1

[0021] Wherein, R1, R2 and R3 are independently selected from a saturated hydrocarbon group having 1-5 carbon atoms, an unsaturated hydrocarbon group having 1-5 carbon atoms or a halogenated hydrocarbon group having 1-5 carbon atoms; and at least one of R1, R2 and R3 is an unsaturated hydrocarbon group.

[0022] In one implementation of the present application, the compound represented by structural formula 1 is specifically at least one of the compounds represented by structural formula A, structural formula B and structural formula C;

[0023] Structural Formula A

[0024] Structural formula B

[0025] Structural formula C

[0026] In one implementation of the present application, the nitrile additive is at least one of the compounds represented by Structural Formula 2, Structural Formula 3, Structural Formula 4 and Structural Formula 5;

[0027] Structural formula 2NC-R4-CN

[0028] Structural formula 3NC-R5-O-R6-O-R7-CN

[0029] Structural formula 4R8-O-R9-CN

[0030] Structural formula 5

[0031] Wherein, in formula 2, R4 is a C1-C8 alkylene group, a C1-C8 alkylene group substituted with a cyano group, a C2-C8 alkenylene group or a C2-C8 alkenylene group substituted with a cyano group; in formula 3, R5, R6 and R7 are each independently selected from a C1-C5 alkylene group or a C2-C5 alkenylene group; in formula 4, R8 is a C2-C5 unsaturated hydrocarbon group, and R9 is a C1-C5 alkylene group; in formula 5, R 10 , R 11 and R 12 Each is independently selected from a C1-C5 alkylene group or a C2-C5 alkenylene group.

[0032] In one implementation of the present application, the compound of structural formula 2 is at least one of the compounds represented by structural formula D, structural formula E, structural formula F, structural formula G and structural formula H;

[0033] Structural formula D

[0034] Structural Formula E

[0035] Structural Formula F

[0036] Structural formula G

[0037] Structural formula H

[0038] In one implementation of the present application, the compound of structural formula 3 is at least one of the compounds represented by structural formula I, structural formula J and structural formula K;

[0039] Structural Formula I

[0040] Structural formula J

[0041] Structural formula K

[0042] In one implementation of the present application, the compound of structural formula 4 is a compound represented by structural formula L;

[0043] Structural formula L

[0044] In one implementation of the present application, the compound of structural formula 5 is a compound represented by structural formula M;

[0045] Structural formula M

[0046] In one implementation of the present application, the lithium salt further includes at least one of LiPO2F2, LiBF4, LiClO4, LiCF3SO3, LiN(SO2CF3)2 and LiN(SO2F)2.

[0047] In one implementation of the present application, the concentration of the lithium salt is 0.5 mol / L to 3.5 mol / L.

[0048] In one implementation of the present application, the non-aqueous organic solvent includes at least one of cyclic carbonates, fluorinated cyclic carbonates, unsaturated cyclic carbonates, cyclic sultones, chain carbonates, carboxylates and ethers; wherein the cyclic carbonate is at least one of ethylene carbonate, propylene carbonate and butylene carbonate; the fluorinated cyclic carbonate is at least one of fluorinated ethylene carbonate, trifluoromethyl ethylene carbonate and bisfluoroethylene carbonate; the unsaturated cyclic carbonate is at least one of vinylene carbonate, ethylene carbonate and methylene carbonate; the cyclic sultone is at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; the chain carbonate is at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

[0049] In one implementation of the present application, the non-aqueous organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

[0050] In one implementation of the present application, the non-aqueous organic solvent is a combination of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate.

[0051] Another aspect of the present application discloses a lithium-ion battery, the shell of which is a nickel-plated steel shell. The lithium-ion battery comprises a nickel-containing ternary positive electrode, a negative electrode, a diaphragm and the non-aqueous electrolyte of the present application.

[0052] It should be noted that the lithium-ion battery of the present application has a good anti-corrosion effect due to the use of the non-aqueous electrolyte of the present application; and greatly reduces the deposition of nickel and iron at the negative electrode, thereby reducing the blockage of the lithium ion conduction path caused by it, reducing the risk of lithium precipitation and safety hazards caused by it; and improving the performance of the lithium-ion battery. In one implementation of the present application, after the lithium-ion battery is cycled for 1000 times at 45°C, the nickel content deposited at the negative electrode is ≤500ppm, and the iron content is ≤100ppm, which is much lower than the nickel and iron deposition of the existing electrolyte under the same conditions.

[0053] In one implementation of the present application, the active material of the nickel-containing ternary positive electrode is LiNi x Co y Mn z O2, 0.5≤x≤1, 0≤y≤0.5, 0≤z≤0.5, 0≤x+y+z≤1.

[0054] In one implementation of the present application, the applicable upper voltage range of the lithium-ion battery is 4.1V-5.5V.

[0055] It should be noted that the lithium-ion battery of the present application, due to the use of the non-aqueous electrolyte of the present application, has better corrosion resistance and can alleviate the corrosion of the nickel metal on the inner wall of the steel shell by the byproducts generated by the decomposition of LiPF6 under high voltage; therefore, it can be used at a higher upper limit voltage.

[0056] Due to the adoption of the above technical solution, the beneficial effects of this application are:

[0057] The non-aqueous electrolyte of the present application utilizes the first additive to inhibit HF generation and play an anti-corrosion role, and utilizes the second additive to form an anti-corrosion film to enhance the anti-corrosion effect; and utilizes the electronegativity of the first additive to participate in and optimize the composition and structure of the anti-corrosion film layer formed by the second additive on the surface of the steel shell, thereby further enhancing the anti-corrosion effect and improving the performance of the battery, especially improving the high-temperature cycle stability and reducing the impedance growth after high-temperature cycling. DETAILED DESCRIPTION

[0058] The key to this application is to add a specific oxalate inorganic lithium salt additive, i.e., the first additive, and an unsaturated phosphate and / or nitrile additive, i.e., the second additive, to the non-aqueous electrolyte. By utilizing the synergistic effect of the first additive and the second additive, the anti-corrosion effect of the nickel-plated steel shell can be further improved, and the deposition of metal ions in the nickel-plated steel shell on the negative electrode after dissolution can be effectively inhibited, thereby improving the performance of the battery, especially improving the high-temperature cycle stability of the battery and reducing the impedance growth after high-temperature cycling.

[0059] All raw materials or equipment used in the examples of this application, unless otherwise specified, are raw materials or equipment that can be purchased from the market or are routinely used in production or testing. The first additive, second additive, structural formula 1 to structural formula 5, and structural formula A to structural formula M in this application are only for the convenience of distinction and description and have no other meaning.

[0060] The present application is further described in detail below through specific examples. The following examples are only used to further illustrate the present application and should not be construed as limiting the present application.

[0061] Embodiment 1

[0062] The non-aqueous electrolyte of this example uses a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) as a non-aqueous organic solvent, and the lithium salt uses lithium hexafluorophosphate (LiPF6) with a concentration of 1 mol / L. The non-aqueous electrolyte is added with a first additive and a second additive, the first additive is a phosphate containing an unsaturated bond, and the second additive is at least one of a nitrile additive and an inorganic lithium salt type additive containing an oxalate. Among them, the phosphate containing an unsaturated bond is a compound shown in structural formula 1, and specifically in this example is at least one of the compounds shown in structural formula A, structural formula B and structural formula C. The inorganic lithium salt type additive containing an oxalate is selected from lithium difluoro oxalate borate, lithium dioxalate borate or lithium difluorobis oxalate phosphate. The nitrile additive is at least one of the compounds shown in structural formula 2, structural formula 3, structural formula 4 and structural formula 5; wherein the compound of structural formula 2 is at least one of the compounds shown in structural formula D, structural formula E, structural formula F, structural formula G and structural formula H, the compound of structural formula 3 is at least one of the compounds shown in structural formula I, structural formula J and structural formula K, the compound of structural formula 4 is the compound shown in structural formula L, and the compound of structural formula 5 is the compound shown in structural formula M.

[0063] The specific additives used in this example and their specific amounts are shown in Table 1.

[0064] The preparation method of the non-aqueous electrolyte in this example specifically includes:

[0065] In a glove box with a water and oxygen content of less than 10 ppm, ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 3:5:2. After cooling, lithium hexafluorophosphate (LiPF6) was added to a concentration of 1 mol / L. Then, the corresponding additives were added according to the ratio in Table 1 to obtain the non-aqueous electrolyte of this example.

[0066] Table 1 Additives and dosage of non-aqueous electrolyte

[0067] serial number Additives and their dosage Cathode Materials Upper limit voltage Test 1 0.2%LiODFB+0.5%Structural Formula D NCM811 4.2V Test 2 0.2%LiODFB+1%Structural Formula D NCM811 4.2V Test 3 0.2%LiODFB+1%Structural Formula A NCM811 4.2V Test 4 1%LiODFB+0.5%Structural Formula D NCM811 4.2V Test 5 0.1%LiODFB+0.1%Structural Formula D NCM811 4.2V Test 6 5%LiODFB+5%Structural Formula D NCM811 4.2V Test 7 8%LiODFB+5%Structural Formula D NCM811 4.2V Test 8 0.2%LiODFB+2%Structural Formula D NCM523 4.2V Test 9 0.2%LiODFB+0.1%Structural Formula D NCM523 4.4V Test 10 0.2%LiODFB+5%Structural Formula D NCM811 4.2V Test 11 0.2%LiODFB+0.05%Structural Formula D NCM811 4.2V Test 12 0.2%LiODFB+8%Structural Formula D NCM811 4.2V Test 13 0.2%LiODFB+0.5%Structural Formula A NCM622 4.2V Test 14 0.2%LiODFB+0.1%Structural Formula A NCM811 4.2V Test 15 0.2%LiODFB+5%Structural Formula A NCM811 4.2V Test 16 0.2%LiODFB+0.05%Structural Formula A NCM811 4.2V Test 17 0.2% LiODFB+8% Structural Formula A NCM811 4.2V Test 18 0.2%LiODFB+1%Structural Formula B NCM811 4.2V Comparison 1 1% Structural Formula A NCM811 4.2V Comparison 2 1% Structural Formula D NCM811 4.2V Contrast 3 1%LiODFB NCM811 4.2V Contrast 4 1% structural formula D + 1% structural formula A NCM811 4.2V Contrast 5 - NCM811 4.2V Contrast 6 - NCM622 4.2V Contrast 7 - NCM523 4.2V

[0068] In Table 1, for example, "0.2% LiODFB + 0.5% structural formula D" in "Test 1" means that 0.2% of LiODFB and 0.5% of the compound represented by structural formula D accounting for the total mass are added to the non-aqueous electrolyte; "1% structural formula A" in "Comparison 1" means that only 1% of the compound represented by structural formula A accounting for the total mass is added to the non-aqueous electrolyte; "-" in "Comparison 5" to "Comparison 7" means that no additives are added to the non-aqueous electrolyte; the rest are similar and are not repeated here. In Table 1, "positive electrode material" "NCM811" refers to a ternary positive electrode material with a ratio of 0.8:0.1:0.1 for nickel (Ni), cobalt (Co) and manganese (Mn); "NCM523" refers to a ternary positive electrode material with a ratio of 0.5:0.2:0.3 for nickel (Ni), cobalt (Co) and manganese (Mn); "NCM622" refers to a ternary positive electrode material with a ratio of 0.6:0.2:0.2 for nickel (Ni), cobalt (Co) and manganese (Mn). In Table 1, "upper limit voltage" refers to the upper limit voltage value of a lithium-ion battery prepared using a corresponding non-aqueous electrolyte.

[0069] In this example, 18 non-aqueous electrolytes were prepared according to the formula in Table 1; at the same time, a non-aqueous electrolyte without additives was used as a comparison, and a non-aqueous electrolyte with only the first additive or only the second additive was used as a comparison. In Table 1, Comparison 1 is a non-aqueous electrolyte with only one second additive, a phosphate ester containing an unsaturated bond, Comparison 2 is a non-aqueous electrolyte with only another second additive, a nitrile additive, Comparison 3 is a non-aqueous electrolyte with only the first additive, and Comparison 4 is a non-aqueous electrolyte with two second additives; Comparisons 5, 6, and 7 are non-aqueous electrolytes without additives, and lithium-ion batteries with different positive electrode materials are used.

[0070] The lithium ion battery preparation method of this example includes:

[0071] The negative electrode of the lithium-ion battery in this example uses graphite and conductive carbon black, and the separator uses a three-layer separator of polypropylene, polyethylene and polypropylene with a thickness of 20 μm.

[0072] The negative electrode preparation method is as follows: graphite, conductive carbon black, binder styrene-butadiene rubber and carboxymethyl cellulose are mixed in a mass ratio of 96:1:1.2:1.8, dispersed in deionized water to obtain a negative electrode slurry, the negative electrode slurry is coated on both sides of the copper foil, and after drying, calendering and vacuum drying, a nickel lead wire is welded with an ultrasonic welder to obtain a negative electrode plate, and the thickness of the plate is between 120-150 μm.

[0073] The battery assembly method is as follows: a three-layer separator with a thickness of 20 μm is placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the separator and the negative plate is wound, and after the winding is completed, it is placed in a nickel-plated steel shell, and the prepared electrolyte is injected into the steel shell battery cell, and after aging, hot pressing, aging, secondary vacuum sealing, and then further charged to 4.2V at a constant current of 0.2C, and after being placed at room temperature for 24 hours, discharged to 3.0V at a constant current of 0.2C to obtain a lithium-ion secondary battery. Among them, the conditions for hot pressing are 0.05C current, 45°C and pressure 3kg / cm 2 Constant current charging for 180 min; 0.2C current, pressure 5kg / cm 2 The battery is charged at a constant current to 3.8 V. The remaining steps refer to the existing lithium-ion battery preparation.

[0074] In this example, lithium-ion batteries using 18 non-aqueous electrolytes from Test 1 to Test 18 were prepared according to Table 1, and lithium-ion batteries were prepared as comparisons using non-aqueous electrolytes without additives and non-aqueous electrolytes with only the first additive or only the second additive.

[0075] All prepared lithium-ion batteries were subjected to high temperature cycle performance tests and corrosion tests, as follows:

[0076] High temperature cycle performance test: Place the battery in a constant temperature oven at 45°C, charge to 4.2V at a constant current of 1C, then charge at a constant voltage until the current drops to 0.02C, then discharge to 3.0V at a constant current of 1C, and repeat this cycle. Record the discharge capacity Q1 and discharge termination internal resistance R1 of the first cycle, as well as the discharge capacity Q2 and discharge termination internal resistance R2 of the last cycle. Calculate the capacity retention rate and impedance growth rate after high temperature cycling according to the following formula:

[0077] Capacity retention rate = Q2 / Q1*100%

[0078] Impedance growth rate = (R2-R1) / R1*100%

[0079] This example specifically tests the capacity retention rate after 800 cycles, and the results are shown in Table 2.

[0080] Battery disassembly after high-temperature cycling to determine corrosion conditions: After the battery that has undergone high-temperature cycling performance testing is discharged at a constant current of 0.2C to 3V, it is disassembled in a fume hood and the corrosion conditions of the steel shell are determined by observing the color and glossiness of the inner wall of the steel shell. The results are shown in Table 2.

[0081] In addition, this example also detects the metal deposition of the negative electrode after the cycle. Specifically, the battery after the cycle is disassembled to obtain the negative electrode, 2g of the negative electrode sheet is cut into pieces, and its weight is set as m1. 30g of nitric acid solution with a mass fraction of 25% is added, and its weight is set as m2. After soaking for 24 hours, 2g of the soaking liquid (set as m3) is taken and diluted to 20g (set as m4) with pure water. The diluted sample is tested by ICP-OES, and the content of nickel and iron elements is appm. The metal content in the negative electrode sheet is calculated as bppm. The calculation formula is as follows:

[0082] b=a*(m4*m2) / (m3*m1)

[0083] Table 2 Test results of capacity retention and corrosion conditions

[0084]

[0085]

[0086] The results in Table 2 show that the dosage of the inorganic lithium oxalate salt additive can be 0.1%-8%; however, too high an amount of the inorganic lithium oxalate salt additive will affect the capacity retention rate, such as in Test 7; therefore, the preferred dosage of the inorganic lithium oxalate salt additive is 0.1%-5%. As for the second additive, the dosage of the nitrile additive can be 0.05%-8%; however, similarly, too low or too high an amount of the nitrile additive will affect the capacity retention rate, such as in Tests 11 and 12, the inorganic lithium oxalate salt additives and their dosages are the same, the dosage of the nitrile additive in Test 11 is 0.05%, which is too low, and the capacity retention rate is only 80.4%, and the dosage of the nitrile additive in Test 12 is 8%, which is too high, and the capacity retention rate is only 80.6%; therefore, the preferred dosage of the nitrile additive is 0.1%-5%. The dosage of the phosphate additive containing an unsaturated bond can be 0.05%-8%; however, similarly, too low or too high a dosage of the phosphate additive containing an unsaturated bond will also affect the capacity retention rate. For example, in Test 16 and Test 17, the oxalate inorganic lithium salt additive and its dosage are the same. The dosage of the unsaturated phosphate in Test 16 is 0.05%, which is too low and the capacity retention rate is only 79.5%. The dosage of the unsaturated phosphate in Test 17 is 8%, which is too high and the capacity retention rate is only 80.6%; therefore, the preferred dosage of the unsaturated phosphate is 0.1%-5%.

[0087] The results in Table 2 show that in Tests 1 to 18 of this example, the anti-corrosion effect is good due to the combination of the first additive and the second additive. After 800 cycles at 45°C, no corrosion occurred in Tests 1 to 18; while corrosion occurred in Comparison 5, Comparison 6 and Comparison 7. By comparing Tests 1 to 18 with Comparisons 1 to 4, it can be clearly seen that the anti-corrosion effect of using the first additive or the second additive alone is poor; thus, the combination of the first additive and the second additive can indeed improve the anti-corrosion effect.

[0088] In addition, by comparing the contents of Fe and Ni in the negative electrode metal ions of Tests 1 to 18 and Comparisons 1 to 7, it can be seen that after a long period of high-temperature cycling, the negative electrode metal ion deposition is less in Tests 1 to 18, while a large amount of metal ion deposition is present in the negative electrodes of Comparisons 1 to 7. It can be seen that the non-aqueous electrolyte in the present application using the first additive and the second additive combination can greatly reduce the deposition of nickel and iron at the negative electrode, thereby reducing the blockage of the lithium ion conduction path caused thereby, and reducing the risk of lithium precipitation and safety hazards caused thereby.

[0089] Embodiment 2

[0090] In this example, based on Experiment 2 and Experiment 3 of Example 1, different additives and their dosages were further tested, as shown in Table 3.

[0091] Table 3 Additives and dosage of non-aqueous electrolyte

[0092] serial number Additives and their dosage Test 19 0.2%LiODFB+1%Structural Formula E Test 20 0.2%LiODFB+1%Structural Formula F Test 21 0.2%LiODFB+1%Structural Formula G Test 22 0.2%LiODFB+1%Structural Formula H Test 23 0.2%LiODFB+1%Structural Formula I Test 24 0.2%LiODFB+1%Structural Formula J Test 25 0.2%LiODFB+1%Structural Formula K Test 26 0.2%LiODFB+1%Structural formula L Test 27 0.2%LiODFB+1%Structural Formula M Test 28 0.2%LiODFB+1%Structural Formula C Test 29 0.2%LiBOB+1%Structural Formula D Test 30 0.2%LiDFOP+1%Structural Formula D Test 31 0.2%LiBOB+1%Structural Formula A Test 32 0.2%LiDFOP+1%Structural Formula A Test 33 1%LiODFB+0.1%Structural Formula D Test 34 1%LiODFB+1%Structural Formula D Test 35 3%LiODFB+3%Structural Formula D Test 36 5%LiODFB+0.2%Structural Formula A Test 37 0.2%LiBOB+1%Structural Formula D+1%Structural Formula A Test 38 0.2% LiBOB + 3% structural formula D + 1% structural formula A

[0093] In Table 3, Tests 19 to 27 are based on Test 2 of Example 1, with one of the structural formulas E to M being substituted for the structural formula D of Test 2 in an equal amount, and the rest are the same as Test 2. Test 28 is based on Test 3 of Example 1, with the structural formula C being substituted for the structural formula A of Test 3 in an equal amount, and the rest are the same as Test 3. Tests 29 and 30 are based on Test 2 of Example 1, with the LiBOB or LiDFOP being substituted for the LiODFB of Test 2 in an equal amount, and the rest are the same as Test 2. Test 31 is based on Test 29, with the structural formula A being substituted for the structural formula D in an equal amount, and the rest are the same as Test 29. Test 32 is based on Test 30, with the structural formula A being substituted for the structural formula D in an equal amount, and the rest are the same as Test 30. Tests 33 to 35 are based on Test 2 of Example 1, with different amounts of LiODFB and structural formula D. Test 36 is based on Test 3 of Example 1, with different amounts of LiODFB and structural formula A. Test 37 is based on Test 2 of Example 1, with 1% of structure A added, and the rest is the same as Test 2. Test 38 is based on Test 37, with the amount of structure D added, and the rest is the same.

[0094] In this example, 20 kinds of non-aqueous electrolytes were prepared according to Table 3, lithium-ion batteries were assembled according to the method of Example 1, and high-temperature cycle performance tests and corrosion tests were performed on the assembled lithium-ion batteries according to the method of Example 1.

[0095] Table 4 Test results of capacity retention and corrosion of lithium-ion batteries with different non-aqueous electrolyte formulations

[0096]

[0097]

[0098] The results in Table 4 show that the capacity retention rate of the lithium-ion batteries using the 20 non-aqueous electrolytes prepared in this example is above 84% after 800 cycles at 45°C, and no shell corrosion occurs after high-temperature cycles. In particular, in Tests 37 and 38, due to the use of oxalate inorganic lithium salt additives, nitrile additives and phosphates containing unsaturated bonds, the three additives not only have a high capacity retention rate; but also, according to observation, there is almost no corrosion on the surface of the nickel-plated steel shell, and the combination of the three additives has a better anti-corrosion effect.

[0099] The above contents are further detailed descriptions of the present application in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present application is limited to these descriptions. For ordinary technicians in the technical field to which the present application belongs, several simple deductions or substitutions can be made without departing from the concept of the present application.

Claims

1. A non-aqueous electrolyte for a lithium-ion battery with a nickel-plated steel shell, characterized in that: The non-aqueous electrolyte comprises a lithium salt, a non-aqueous organic solvent, and an additive accounting for 0.2% to 20% of the total mass of the non-aqueous electrolyte; The lithium salt comprises at least lithium hexafluorophosphate; The additives include a first additive and a second additive; The first additive is at least one of lithium difluorooxalatoborate, lithium dioxalatoborate and lithium difluorobisoxalatophosphate; The second additive is a nitrile additive, and the nitrile additive is at least one of the compounds represented by structural formula D, structural formula E, structural formula F, structural formula G, structural formula H, structural formula I, structural formula J, structural formula K, structural formula L and structural formula M; The first additive accounts for 0.2%-5% of the total mass of the non-aqueous electrolyte, and the nitrile additive accounts for 0.1%-5% of the total mass of the non-aqueous electrolyte.

2. The non-aqueous electrolyte according to claim 1, characterized in that: The second additive consists of a nitrile additive and a phosphoric acid ester containing an unsaturated bond.

3. The non-aqueous electrolyte according to claim 2, characterized in that: The phosphate containing unsaturated bonds accounts for 0.1%-5% of the total mass of the non-aqueous electrolyte.

4. The non-aqueous electrolyte according to claim 2, characterized in that: The phosphate containing an unsaturated bond is at least one of the compounds shown in Structural Formula 1; Wherein, R1, R2 and R3 are independently selected from a saturated hydrocarbon group having 1-5 carbon atoms, an unsaturated hydrocarbon group having 1-5 carbon atoms or a halogenated hydrocarbon group having 1-5 carbon atoms; and at least one of R1, R2 and R3 is an unsaturated hydrocarbon group.

5. The non-aqueous electrolyte according to claim 4, characterized in that: The compound represented by the structural formula 1 is specifically at least one of the compounds represented by the structural formula A, the structural formula B and the structural formula C; 6. The non-aqueous electrolyte according to any one of claims 1 to 5, characterized in that: The lithium salt also includes at least one of LiPO2F2, LiBF4, LiClO4, LiCF3SO3, LiN(SO2CF3)2 and LiN(SO2F)2.

7. The non-aqueous electrolyte according to claim 6, characterized in that: The concentration of the lithium salt is 0.5 mol / L to 3.5 mol / L.

8. The non-aqueous electrolyte according to any one of claims 1 to 5, characterized in that: The non-aqueous organic solvent includes at least one of cyclic carbonates, fluorinated cyclic carbonates, unsaturated cyclic carbonates, cyclic sultones, chain carbonates, carboxylates and ethers; The cyclic carbonate is at least one of ethylene carbonate, propylene carbonate and butylene carbonate; The fluorinated cyclic carbonate is at least one of fluoroethylene carbonate, trifluoromethylethylene carbonate and bisfluoroethylene carbonate; The unsaturated cyclic carbonate is at least one of vinylene carbonate, vinyl ethylene carbonate and methylene carbonate; The cyclic sultone is at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; The chain carbonate is at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

9. The non-aqueous electrolyte according to claim 8, characterized in that: The non-aqueous organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

10. The non-aqueous electrolyte according to claim 9, characterized in that: The non-aqueous organic solvent is a combination of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate.

11. A lithium-ion battery, wherein the outer shell of the lithium-ion battery is a nickel-plated steel shell, characterized in that: The lithium-ion battery comprises a nickel-containing ternary positive electrode, a negative electrode, a separator and the non-aqueous electrolyte according to any one of claims 1 to 10.

12. The lithium-ion battery according to claim 11, characterized in that: The active material of the nickel-containing ternary positive electrode is LiNi x Co y Mn z O2, 0.5≤x≤1, 0≤y≤0.5, 0≤z≤0.5, 0≤x+y+z≤1.

13. The lithium ion battery according to claim 11 or 12, characterized in that: The applicable upper voltage range of the lithium-ion battery is 4.1V-5.5V.